Mortality rates from cryptogenic fibrosing alveolitis in seven countries. - RB Hubbard; Andrew Johnston; David Coultas; John Britton (1996)
Registered mortality from cryptogenic fibrosing alveolitis (CFA) in England and Wales has increased substantially since the specific International Classification of Diseases code for CFA was introduced in 1979. However, since a significant proportion of deaths from CFA are misclassified as post inflammatory fibrosis (PIF), it is possible that the observed rise in CFA mortality is due to diagnostic transfer from this code. To investigate this, and to assess mortality trends in other countries, annual CFA and PIF mortality data from England and Wales, USA, Australia, Scotland, Canada, New Zealand, and Germany were analysed.Crude annual mortality rates were calculated and rates standardised by Poisson regression to allow assessment of changes over time and comparison between countries, sexes, and age groups. The relative trends in mortality from CFA and PIF were assessed by calculating the annual ratio of CFA to PIF deaths.Men were more likely than women to die from both CFA and PIF in all countries. The highest standardised CFA mortality rate occurred in England and Wales, and the lowest in Germany. Since 1979 mortality from CFA has increased in England and Wales, Australia, Scotland and Canada, but there was no trend in CFA mortality in New Zealand or Germany. In the USA mortality from CFA was low and has fallen. Mortality from PIF increased in all countries except New Zealand and Germany, and the highest PIF mortality, together with the greatest increase over time, was seen in the USA. Changes over time in the annual ratio of CFA to PIF deaths in all countries were small, implying that diagnostic transfer is not a major cause of the increasing CFA mortality.Mortality from CFA continues to increase in England and Wales and in many other countries. Diagnostic transfer from PIF does not appear to be a major cause of this.